Fab-Nanolipoprotein Conjugate Causes Vitreous Opacity and Cataracts Following a Single Intravitreal Administration in New Zealand White Rabbits. (April 2021) - Tassew, Nardos G.; Laing, Steven T.; Shatz, Whitney; Crowell, Susan R.; Loyet, Kelly M.; Schuetz, Chris; Blanchette, Craig
One strategy employed to prolong the ocular half-life of large molecule therapeutics is via covalent attachment to a carrier, resulting in an increase in size thereby slowing their clearance from the eye. Rabbit antigen-binding fragment conjugated to nanolipoprotein (RabFab-NLP) is a novel conjugate intended to prolong ocular half-life through an increase in hydrodynamic radius compared to Fab alone (∼12 vs ∼3 nm). Nanolipoproteins are mimetics of endogenous high-density lipoproteins and consist of lipids and apolipoproteins (ApoE422k), both biologically derived materials. The objective of this study was to evaluate the ocular toxicity and toxicokinetics of RabFab-NLP after a single intravitreal administration in New Zealand White rabbits. Serum toxicokinetic data suggested a significant increase in ocular residence time of RabFab-NLP compared to RabFab alone. Ophthalmic examinations showed that RabFab-NLP caused vitreous and lens opacities as early as day 3 and day 8 postdose, respectively, which persisted for the entire study duration to day 30. The RabFab-NLP-related microscopic findings were present in the lens, vitreous cavity, and/or optic nerve head. Based on the observed ocular toxicity, a single intravitreal dose of 1.3 mg/eye RabFab-NLP was not tolerated and caused vitreous opacity and cataracts in rabbit eyes.